Constitutional origin and norm creation in Colombia : discursive institutionalism and the empowerment of the Constitutional Court - Boesten, Jan (Abingdon, Oxon ; New York, NY : Routledge, 2022)
This book explains the growing empowerment of the Colombian Constitutional Court in the early years of the 21st century and develops the concept of the deliberative judge. Taking the case of the Colombian Constitutional Court and drawing on neoinstitutional theory to explain the relationship between political crisis and institutional reforms, the book challenges the notion of rational choice institutionalism that agents act strategically. It indicates the limits of path dependence and argues instead that discursive institutionalism is the most appropriate method for analyzing processes of institutional learning. Combining theoretical and empirical research, it builds the argument that judicial independence promotes the case for deliberative democracy over rational choice or strategic action approaches. Finally, the book suggests that by introducing communicative and cognitive variables in our understanding of key actors and processes, we are more capable of bridging institutional origin and legacy. The work will be a valuable resource for academics, researchers, and policy-makers in Constitutional Law, Constitutional Politics, and Constitutional History.
Introduction : ethical legal discourse in delegative democracies -- The novelty of the 1991 Constitution : a critical juncture in Colombia's history -- The choque de trenes between Colombia's high courts : path dependence and legal argumentation -- Discursive institutionalism in Colombia's Constitutional Court : the deliberative judge and norm creation in a politicized context -- Conclusion : the preeminence of democratic legality over democratic security and discursive institutionalism -- Epilogue.
Based on author's thesis (doctoral - University of British Columbia, 2016) issued under title: Between democratic security and democratic legality : discursive institutionalism and Colombia's Constitutional Court.
Keywords: Colombia. -- Corte Constitucional; Constitutional courts -- Political aspects -- Colombia; Political questions and judicial power -- Colombia; LAW / General; LAW / Comparative; LAW / Constitutional